(untitled) (Petaling Jaya, Selangor, Malaysia, 2007)
This book compiles together the statutory provisions and forms which are used in making common applications in civil proceedings. It is intended for all who undertake civil matters,..
Keywords: Civil procedure,Court rules,Thủ tục tố tụng dân sự; Forms; Malaysia,Malaysia,Malaysia